2018
DOI: 10.1002/ijgo.12478
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betamethasone on fetoplacental and maternal hemodynamics in preterm pregnancies

Abstract: Betamethasone had favorable effects on fetal cerebral circulation, with increased end-diastolic velocity in the middle cerebral artery; this could represent a positive effect on cerebral blood circulation and decreased flow resistance in the umbilical artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
2
1
1
Order By: Relevance
“…Therefore, betamethasone could influence brain circulation. Concordant with the literature, DV PI remained unchanged in the present study [11,12,14,15].…”
Section: Division Of Worksupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, betamethasone could influence brain circulation. Concordant with the literature, DV PI remained unchanged in the present study [11,12,14,15].…”
Section: Division Of Worksupporting
confidence: 92%
“…Another study reported that umbilical artery PI was decreased in fetuses that develop RDS in the neonatal period [9]. İnan et al detected no significant change at umbilical PI, but there was a significant change at RI [15]. In our study, we detected no significant differences in the umbilical artery Doppler indices before and after steroid administration.…”
Section: Division Of Workcontrasting
confidence: 58%
See 1 more Smart Citation
“…The haemodynamic effect of corticosteroids at foetal and postnatal level is well known [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The results of our investigation found greater haemodynamic stability, and a tendency to a better evolution of respiratory distress syndrome in the 12 h betamethasone group.…”
Section: Discussionmentioning
confidence: 99%